2008
DOI: 10.1037/0097-7403.34.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory and inhibitory learning with absent stimuli.

Abstract: Three experiments show that two associatively-activated stimulus representations may engage in excitatory or inhibitory learning, depending on their temporal relationship. Experiment 1a suggested that simultaneously-activated stimulus representations show evidence of inhibitory learning in an acquisition test. Experiment 1b showed similar evidence of inhibition in a summation test. Experiment 2 found that activation of two stimulus representations in a serial compound resulted in excitatory learning between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
18
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 45 publications
6
18
2
Order By: Relevance
“…Although simultaneous presentations of CSs and USs have often been found to yield excitatory learning (e.g., Heth, 1976), some studies have observed inhibitory learning (e.g., Heth, 1976; Moscovitch & LoLordo, 1968). Most important, our observation of inhibitory learning when two event representations are simultaneously activated into the A2 sate is consistent with the observations of Wheeler et al (2008). Those authors, using sensory preconditioning procedures, also found inhibitory A2-A2 learning after simultaneous or backward pairings of surrogate events.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Although simultaneous presentations of CSs and USs have often been found to yield excitatory learning (e.g., Heth, 1976), some studies have observed inhibitory learning (e.g., Heth, 1976; Moscovitch & LoLordo, 1968). Most important, our observation of inhibitory learning when two event representations are simultaneously activated into the A2 sate is consistent with the observations of Wheeler et al (2008). Those authors, using sensory preconditioning procedures, also found inhibitory A2-A2 learning after simultaneous or backward pairings of surrogate events.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of those noise-tone associations was revealed by subsequent tone-food conditioning, followed by tests of responding to the noise, as in sensory preconditioning experiments. Analogous to the results of the present experiments, Wheeler et al (2008) found excitatory noise-tone associations when noise and tone surrogates were presented in a forward manner, but inhibitory noise-tone associations when they were presented simultaneously or in backward order. Wheeler et al (2008) raised the possibility that their results may have depended on their use of sensory preconditioning procedures, in which both events represented in the A2 state were of relatively neutral value.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Holmes et al,, 2010), then these representations of SI and S2 will be activated during later instrumental training when Rl is paired with 01 and R2 is paired with O2, This should allow Sl-Rl and S2-R2 to form. Whatever the order in which Pavlovian and Instrumental training takes place, the process of mediated stimulus-response leaming (see Holland, 1981Holland, , 1983Iordanova, Good, & Honey, 2011;Wheeler, Sherwood, & Holland, 2008; but see, Wagner, 1981) will depend upon the stimuli (or their evoked memories) and responses (or their corresponding motor programs) occurring in close temporal contiguity. Importantly, the influence of the mediated Sl-Rl and S2-R2 associations on instmmental performance will be unaffected by outcome devaluation before the PIT test (Colwill & Rescorla, 1990;Rescorla, 1994;Holland, 2004), Moreover, to the extent that S-R associations are relatively insensitive to extinction, presentations of the stimuli before the PIT test might not infiuence the likelihood of observing outcome-selective PIT in spite of the fact that they should undermine the efficacy of the S-O association during the test (see Delamater, 1996),…”
mentioning
confidence: 99%